2016
DOI: 10.1021/acs.est.6b01674
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Gas-Particle Partitioning of Tracers for Biogenic Oxidation

Abstract: Exchange of atmospheric organic compounds between gas and particle phases is important in the production and chemistry of particle-phase mass but is poorly understood due to a lack of simultaneous measurements in both phases of individual compounds. Measurements of particle- and gas-phase organic compounds are reported here for the southeastern United States and central Amazonia. Polyols formed from isoprene oxidation contribute 8% and 15% on average to particle-phase organic mass at these sites but are also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 76 publications
13
122
1
1
Order By: Relevance
“…To achieve this end, atmospheric models routinely rely on estimates of volatility (i.e., vapor pressure or saturation concentration) and solubility in a predominantly aqueous phase. Although research efforts demonstrate clearly the importance of organic solubility in water on phase partitioning and particle viscosity Hodas et al, 2015;Pajunoja et al, 2015;Riipinen et al, 2015;Wania et al, 2015;Isaacman-VanWertz et al, 2016;Jathar et al, 2016b;Pye et al, 2017;Shiraiwa et al, 2017), improvements to the conceptual model of organic compounds partitioning into an organic-rich particulate phase alone are useful before the entire system is treated holistically.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this end, atmospheric models routinely rely on estimates of volatility (i.e., vapor pressure or saturation concentration) and solubility in a predominantly aqueous phase. Although research efforts demonstrate clearly the importance of organic solubility in water on phase partitioning and particle viscosity Hodas et al, 2015;Pajunoja et al, 2015;Riipinen et al, 2015;Wania et al, 2015;Isaacman-VanWertz et al, 2016;Jathar et al, 2016b;Pye et al, 2017;Shiraiwa et al, 2017), improvements to the conceptual model of organic compounds partitioning into an organic-rich particulate phase alone are useful before the entire system is treated holistically.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have indicated that HMML may be a more dominant precursor to 2-MG (Nguyen et al, 2015). Additionally, we assume that the products of these aerosol and cloud aqueous pathways are nonvolatile, while monomeric species like 2-methyltetrols and 2-MG may be better represented as semivolatile (Isaacman-Van Wertz et al, 2016). These are areas that may be worthwhile to further refine in future development efforts, as more laboratory/field research becomes available, in an effort to better quantify the relative impacts of cloud vs. aerosol water production pathways on SOA mass.…”
Section: Impact Of Cloud Soa Formation Pathway From Biogenic Epoxidesmentioning
confidence: 98%
“…In an effort to determine the optimal solver for our mechanism, we applied each KPP Rosenbrock solver with a positive definite adjustment (Sander et al, 2011) to over 20 000 scenarios (Table S5) representing a range of atmospheric conditions and then compared the results to a reference solution generated with the variable-coefficient ordinary differential equation solver (VODE). VODE is an initial-value ODE solver that uses variable-coefficient backward differentiation formula (BDF) methods for stiff systems and may be viewed as a successor to the Livermore solver for ordinary differential equations (LSODE) (Hindmarsh, 1983), which historically has been commonly applied to generate reference solutions for atmospheric chemistry problems (Brown et al, 1989;Sandu et al, 1997b). DVODE (VODE with double precision) was downloaded from the Netlib repository (http://www.netlib.org) and applied to the rate equations and Jacobian for the system of AQCHEM − KMT reactions to generate a reference solution as well as provide an independent check on the codes Table 2.…”
Section: Solver Selection and Tolerance Settingsmentioning
confidence: 99%
“…Particle-phase composition is therefore critical for studying the importance of individual terpenes and terpene classes, but the dynamic gas-particle partitioning of these semi-volatile products requires the contemporaneous measurement of the difficult-to-measure gasphase components. Measurements of gas-particle partitioning and concentrations of biogenic OA tracers from isoprene and monoterpene oxidation have been reported previously as part of the Green Ocean Amazon (GoAmazon2014/5) field campaign (Isaacman-VanWertz et al, 2016), but few, if any, sesquiterpene oxidation products were identified in the dataset at that time. To fully characterize the sources of OA in the region, molecular-level and chemically specific signatures of oxidation products from a more complete range of BVOC precursors need to be identified and quantified.…”
Section: Introductionmentioning
confidence: 95%
“…Details of the instrument development and operation have been published previously (Isaacman-VanWertz et al, 2016;Isaacman et al, 2014;Kreisberg et al, 2009;Williams et al, 2006;Zhao et al, 2013) and we describe SV-TAG deployment briefly here. During the campaign, ambient air was pulled through a 15.24 cm ID duct at ∼ 5 m above ground level.…”
Section: Deployment Of a Semi-volatile Thermal Desorption Aerosol Gasmentioning
confidence: 99%